Train the engine or the brakes? Influence of momentum on the change of direction deficit - Fernandes, R.; Bishop, C.; Turner, A. N.; Chavda, S.; Maloney, S. J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Currently, it is unclear which physical characteristics may underpin the change of direction deficit (COD-D). This investigation sought to determine if momentum, speed-, and jump-based measures may explain variance in COD-D. Methods: Seventeen males from a professional soccer academy (age, 16.76 [0.75] y; height, 1.80 [0.06] m; body mass, 72.38 [9.57] kg) performed 505 tests on both legs, a 40-m sprint, and single-leg countermovement and drop jumps. Results: The regression analyses did not reveal any significant predictors for COD-D on either leg. "Large" relationships were reported between the COD-D and 505 time on both limbs (r = .65 to .69; P < .01), but COD-D was not associated with linear momentum, speed-, or jump-based performances. When the cohort was median split by COD-D, the effect sizes suggested that the subgroup with the smaller COD-D was 5% faster in the 505 test (d = -1.24; P < .001) but 4% slower over 0-10 m (d = 0.79; P = .33) and carried 11% less momentum (d = -0.81; P = .17). Conclusion: Individual variance in COD-D may not be explained by speed- and jump-based performance measures within academy soccer players. However, when grouping athletes by COD-D, faster athletes with greater momentum are likely to display a larger COD-D. It may, therefore, be prudent to recommend more eccentric-biased or technically focused COD training in such athletes and for coaches to view the COD action as a specific skill that may not be represented by performance time in a COD test.